2002
DOI: 10.1046/j.1365-2982.2002.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin type‐4 receptors modulate the sensitivity of intramural mechanoreceptive afferents of the cat rectum

Abstract: It has been suggested that serotonin (5-hydroxytryptamine) type-4 (5-HT4) receptors modulate the sensitivity of intrinsic afferents of the intestinal mucosa. We studied the involvement of 5-HT4receptors in the modulation of extrinsic afferent sensitivity of the intestinal wall. During distension ramps, mechanoreceptive rectal afferents in sacral dorsal roots were examined in decerebrate anaesthesia-free cats using the selective 5-HT4receptor partial agonist, tegaserod (HTF 919), and the 5-HT4receptor antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 39 publications
0
67
0
Order By: Relevance
“…24 5-HT 4 receptor agonists and CGRP have also been suggested to have antinociceptive properties. [10][11][12] Tegaserod, a 5-HT 4 agonist, increased the pain threshold of awake rats subjected to colorectal distention without modifying rectal compliance. 12 Therefore, together with these results, the effect of DKT, which attenuates colorectal distention-induced VMRs, may be mediated through the action of the 5-HT 4 receptor and/or CRD, colorectal distention; ACTH, adrenocorticotropic hormone; DKT, Dai-kenchu-to.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 5-HT 4 receptor agonists and CGRP have also been suggested to have antinociceptive properties. [10][11][12] Tegaserod, a 5-HT 4 agonist, increased the pain threshold of awake rats subjected to colorectal distention without modifying rectal compliance. 12 Therefore, together with these results, the effect of DKT, which attenuates colorectal distention-induced VMRs, may be mediated through the action of the 5-HT 4 receptor and/or CRD, colorectal distention; ACTH, adrenocorticotropic hormone; DKT, Dai-kenchu-to.…”
Section: Discussionmentioning
confidence: 99%
“…Visceromotor responses were analyzed using electromyography in response to colorectal distention (10,20, 40, 60, and 80 mmHg for 20 seconds at 3-minutes intervals). Anxiety-related behavior was measured during exposure to an elevated-plus maze after colorectal distention.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that altered EC cells or 5-HT might be one pathophysiologic mechanism contributing to visceral pain in PI-IBS. More than 90% of 5-HT in the body is secreted from EC cells which are located within the mucosal mucosa, and the tryptophan hydroxylase (TPH) which in EC cells is the rate-limiting enzyme in the 5-HT synthesis process (5)(6)(7). Moreover, recent studies indicated that CD4 + T cells played an important role in the development of colonic EC cell hyperplasia in intestinal infection, and EC cells were influenced by helper T-cell subtype 1 (Th1) or subtype 2 (Th2) cytokine predominant environments (8,9).…”
Section: Introductionmentioning
confidence: 99%